Changes in the dynamics of dengue incidence in South and Central America are possibly due to cross‐population immunity after Zika virus epidemics. Issue 3 (30th November 2020) - Mugabe, Vánio A.; Borja, Lairton S.; Cardoso, Cristiane W.; Weaver, Scott C.; Reis, Mitermayer G.; Kitron, Uriel; Ribeiro, Guilherme S.
Abstract: Objective: We tested the hypothesis that Zika virus (ZIKV) immunity may protect against dengue virus (DENV) infection, disease severity or human amplification, based on analysis of epidemiological data from our long‐term surveillance study (2009–2016) in the city of Salvador, Brazil, that indicated a substantial reduction in the frequency of laboratory‐confirmed dengue cases following the Zika outbreak. To assess whether similar patterns were observed across the Americas, we did a broader explorative investigation of historical series (2004 to 2019) of suspected cases of dengue fever, covering 20 DENV‐endemic South and Central American countries. Methods: We used segmented linear regressions of single group interrupted time series (ITS) analysis to evaluate whether the Zika epidemic had a statistical effect on the trends of annual dengue incidence. Results: We observed in our 16‐year historical series that in all countries, the incidence of dengue exhibited periodic oscillations over time, with a general trend of statistically significant increase during the pre‐Zika period overall and for 11 of the 20 countries. Following the peak of the first population exposure to ZIKV in the Americas, in 2016, the overall rate of reported dengue cases in 2017 and 2018 in the countries under study sharply dropped ( P < 0.05) and was the lowest reported since 2005. Individually in each country, a statistically significant reduction in the annual dengue incidence beginning in 2016 or in 2017–2018 occurred in 13 of the 20 studied countries. However, in 2019, reports of suspected dengue cases increased across the Americas. In Brazil, Dominican Republic, Guatemala and Honduras, dengue incidence was >5 times higher in 2019 than in 2017 and 2018, and, in 2019, they had the greater dengue incidence than in all previous years throughout the historical series. Conclusions: The widespread decline in suspected dengue cases recorded in 2017 and 2018 lends further support to our previous epidemiological hypothesis of ZIKV‐induced cross‐species immunity to DENV. However, the cross‐protection appears to be transient (around 2 years). Long‐term, prospective follow‐ups of dengue reports are needed to confirm (or refute) these findings, which could have significant public health implications, in particular regarding DENV vaccine development and application. Abstract : Contexte: Nous avons émis l'hypothèse que l'immunité contre le virus Zika (ZIKV) pourrait protéger contre l'infection par le virus de la dengue (DENV), la sévérité de la maladie ou l'amplification humaine, sur la base de l'analyse des données épidémiologiques de notre étude de surveillance à long terme (2009‐2016) dans la ville de Salvador, au Brésil, qui a indiqué une réduction substantielle de la fréquence des cas de dengue confirmés en laboratoire à la suite de l'épidémie de Zika. Méthodes: Pour évaluer si des tendances similaires ont été observées dans les Amériques, nous avons mené une enquête exploratoire plus large sur des séries historiques (2004 à 2019) de cas suspects de dengue, couvrant 20 pays d'Amérique du Sud et d'Amérique centrale endémiques pour DENV. Nous avons utilisé des régressions linéaires segmentées de l'analyse des séries chronologiques interrompues pour un seul groupe pour évaluer si l'épidémie de Zika avait un effet statistique sur les tendances de l'incidence annuelle de la dengue. Résultats: Nous avons observé dans notre série historique de 16 ans que dans tous les pays, l'incidence de la dengue présentait des oscillations périodiques au fil du temps, avec une tendance générale à une augmentation statistiquement significative pendant la période pré‐Zika en général et pour 11 des 20 pays. Après le pic de la première exposition de la population au ZIKV dans les Amériques en 2016, le taux global des cas de dengue rapportés en 2017 et 2018 dans les pays étudiés a fortement diminué ( p <0, 05) et était le plus bas depuis 2005. Individuellement dans chaque pays, une réduction statistiquement significative de l'incidence annuelle de la dengue à partir de 2016 ou en 2017‐2018 s'est produite dans 13 des 20 pays étudiés. Cependant, en 2019, les reports de cas suspects de dengue ont augmenté dans les Amériques. Dans des pays comme le Brésil, la République Dominicaine, le Guatemala et le Honduras, l'incidence de la dengue était >5 fois plus élevée en 2019 qu'en 2017 et 2018, et, en 2019, l'incidence de la dengue était plus élevée qu'au cours de toutes les années précédentes de la série historique. Conclusions: Le déclin généralisé des cas suspects de dengue enregistrés en 2017 et 2018 vient étayer notre hypothèse épidémiologique précédente de l'immunité inter‐espèces induite par le ZIKV contre le DENV. Cependant, la protection croisée semble être transitoire (environ 2 ans). Des suivis prospectifs à long terme des reports sur la dengue sont nécessaires pour confirmer (ou réfuter) ces résultats, qui pourraient avoir des implications importantes pour la santé publique, en particulier en ce qui concerne le développement et l'application d'un vaccin DENV.